REQUIREMENTS FOR CONTRIBUTIONS TO “ACTA PAEDAGOGICA VILNENSIA” - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 2015)
The length of the contributions is not to exceed one quire (approx. 40 000 characters). Submitted articles have to meet general structural requirements for research papers and contain a clearly formulated and substantiated research problem, determined research object and aims, defined research methodological principles, methods and the sampling. The concrete aims of the article must be defined and results substantiating them have to be presented; the paper has to include conclusions and a list of references. Considering the above mentioned, the material in the manuscript has to be presented in the following order: Title of the article. Author(s) name, surname, research title, affiliations and addresses (including e-mail address and telephone number). Abstract in the original language of the paper (approx. 500 characters) and keywords (5–6 words). Introduction of the paper, analysing the relevance of the issue in question as of research problem and substantiating formulations of base components (object and aim) of research into the analysed problem. Content of the paper (with its structural parts answering the objectives of the paper). List of references in an alphabetical order (firstly, following the alphabets of the Lithuanian and Latin languages, then those of other languages). The list of literature sources should include all the references mentioned in the paper and the ones not referred to in it are not to be listed. In case the place of publication is presented, the title of a publisher has also to be provided. Abstract of the paper (at least 1600 characters) in English. If the paper is written in English or other main languages of the world (German, French, Russian), the abstract is to be in Lithuanian. Referring to other authors in the text, references to concrete sources should be also provided, with the date of publication in the brackets, following the name of the author. Moreover, when reference to the source of 2 authors is mentioned, the names of both are to be provided in the brackets. In case, the reference is made to 3–5 authors, the first time the names of all the authors have to be included; then, only the first author should be mentioned followed by ‘et al’. If a source has been written by 6 authors, only the name of the first one is mentioned adding ‘et al’ in all the cases of reference. Provided the source has no authors, the title of it and the year of publication are to be indicated in the text. Providing exact quotation from the source by another author, it is necessary to point out the page number. Referring to different publication by the same author published in the same year, the letters a, b, c, etc. have to follow the year of publication. Manuscripts have to include a separate section with data on the author(s) (up to 500 characters) in Lithuanian and English. Next to the full name, research title and degree, institution address and title of the position, research interests should be presented. One review by a qualified specialist in the field (not included into the Editorial board of the journal) is obligatory. The metrics of the paper has to provide the date of its submission to the Editorial Board and the date of its acceptance for publication. The articles of the publication are freely accessed through the website of the university and are included into Lithuanian and foreign databases. The papers in the website of the university are only to be used for research purposes, studies and self-education. Quoting the information, references to the author (authors) and the source of information are obligatory.